PENGEMBANGAN DASHBOARD TRIVY BERBASIS WEBSITE MENGGUNAKAN REACT JS DAN GOLANG - Aquenov Alexandro Kroons; Christine Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Container images can help developers in application development. In creating a container image, it is necessary to perform security checks before it can be used by others. This makes it important for the team to find a solution by detecting the vulnerability of the container image used. Trivy aims to scan container image vulnerabilities and uses the Common Vulnerabilities and Exposures (CVE) database as information from the vulnerabilities found in the container image. This research tries to design a dashboard using React JS and Golang as programming languages to build the frontend and backend sides and use Trivy which is a command line interface-based tool to check the vulnerability of container images. The research was conducted using the Software Development Life Cycle (SDLC) method. This research produces a website-based dashboard that has a user-friendly interface and can be used without any operating system restrictions.